1991
DOI: 10.1001/archderm.1991.01680070039003
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acanthosis Nigricans With Tretinoin

Abstract: A 55-year-old Indian man presented to the dermatology service at The Johns Hopkins Hospital, Baltimore, Md, with a chief complaint of discoloration and thickening of the skin of his axillae, popliteal fossae, the dorsal surface of his toes, and the posterior aspect of his neck. He also complained of a generalized darkening of his complexion. These changes began 12 weeks after starting nicotinic acid, at an oral dose of 500 mg three times a day, for the treatment of hypercholesterolemia. After 16 weeks of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…The lesions were gradually flattened and the brownish pigmentation was decreased after topical treatment with tretinoin. This was probably due to shedding of hyperkeratotic squamae, as was suggested in a previous report 11 .…”
Section: Case Reportsupporting
confidence: 68%
See 1 more Smart Citation
“…The lesions were gradually flattened and the brownish pigmentation was decreased after topical treatment with tretinoin. This was probably due to shedding of hyperkeratotic squamae, as was suggested in a previous report 11 .…”
Section: Case Reportsupporting
confidence: 68%
“…But further studies on unilateral nevoid AN are necessary to determine the pathogenesis. Although no guideline or consensus for the treatment of unilateral nevoid AN has been proposed due to its rare incidence, a case of ordinary AN treated with topical tretinoin was reported in 1991 11 . Moreover, Lee et al 5 achieved clinical improvement with topical tretinoin treatment in a patient with unilateral nevoid AN.…”
Section: Case Reportmentioning
confidence: 99%
“…It has been reported that the etretinate therapy improved glucose tolerance and insulin responses in pa tients with psoriasis [20], Impaired glucose tolerance in our case, however, remained during and after the etretinate therapy. Since retinoids have beneficial effects on various keratinization disorders including AN [21,22], our ther apeutic efficacy might support the concept of CRP as being the keratinization defect. Weight reduction diet therapy occasionally improves the lesion.…”
Section: Discussionmentioning
confidence: 68%
“…We treated her with topical tretinoin because of the favorable response to many hyperkeratotic skin conditions, such as acanthosis nigricans or psoriasis. The effects of topical tretinoin on the epidermis include the induction of epidermal mitotic activity, the shedding of desmosomes and tonofibrils, and the production of a mucin-like material 16 . These actions affect cell growth, differentiation, and morphogenesis and alter cell cohesiveness 17 .…”
Section: Discussionmentioning
confidence: 99%